Attenuation of Seismic Waves in Partially Saturated Berea Sandstone as a Function of Frequency and Confining Pressure - Tisato, Nicola; Madonna, Claudio; Saenger, Erik H. (Frontiers in Earth Science, 2021)
Frequency-dependent attenuation (1/Q) should be used as a seismic attribute to improve the accuracy of seismic methods and imaging of the subsurface. In rocks, 1/Q is highly sensitive to the presence of saturating fluids. Thus, 1/Q could be crucial to monitor volcanic and hydrothermal domains and to explore hydrocarbon and water reservoirs. The experimental determination of seismic and teleseismic attenuation (i.e., for frequencies <100 Hz) is challenging, and as a consequence, 1/Q is still uncertain for a broad range of lithologies and experimental conditions. Moreover, the physics of elastic energy absorption (i.e., 1/Q) is often poorly constrained and understood. Here, we provide a series of measurements of seismic wave attenuation and dynamic Young’s modulus for dry and partially saturated Berea sandstone in the 1-100 Hz bandwidth and for confining pressure ranging between 0 and 20 MPa. We present systematic relationships between the frequency-dependent 1/Q and the liquid saturation, and the confining pressure. Data in the seismic bandwidth are compared to phenomenological models, ultrasonic elastic properties and theoretical models for wave-induced-fluid-flow (i.e., squirt-flow and patchy-saturation). The analysis suggests that the observed frequency-dependent attenuation is caused by wave-induced-fluid-flow but also that the physics behind this attenuation mechanism is not yet fully determined. We also show, that as predicted by wave-induced-fluid-flow theories, attenuation is strongly dependent on confining pressure. Our results can help to interpret data for near-surface geophysics to improve the imaging of the subsurface.